Aplikasi Pengenalan Dan Pembelajaran Alat Musik Tradisional Menggunakan Augmented Reality Berbasis Android - Wafumilena, Vanry Jhon Muda; Lahallo, Jim; Tatuhey, Emy L. (Jurnal Informatika dan Komputer, 2025)
The Android-Based Traditional Musical Instrument Introduction and Learning Application Using Augmented Reality was developed to help students of SMP YPK Hedam Abepura learn traditional Indonesian musical instruments. The app uses Augmented Reality (AR) technology to display 3D models of traditional musical instruments and their related information in real-time. This research aims to build a system that can help students get to know and learn traditional Indonesian musical instruments in an interactive and fun way. The system uses the marker-based AR method, where the user points the Android device's camera at a marker printed on paper or other media. The system then displays a 3D model of the traditional musical instrument and related information, such as name, regional origin, how to play, and the sound of the musical instrument.This application is expected to help students of SMP YPK Hedam Abepura to get to know various kinds of traditional Indonesian musical instruments Learn how to play traditional musical instruments Increase interest and love for the nation's culture This research uses waterfall research methods and system design using Unified Modelling Language (UML). System functionality testing is done with Blackbox testing.